Cizvit Misyonerlerinin Kayseri’deki Eğitim Faaliyetleri: II. Abdülhamid Dönemi - Tekin, Zeki; Karaca, Ayşe Mine (Journal of History Culture and Art Research, 2019)
Education Activities of Jesuit Missionaries in Kayseri During the Reign of the Abdulhamid II Abstract In the late sixteenth century, Catholic Jesuit Missionaries who were active in the Ottoman Empire lands gained momentum after capitulation regulation concerning religious freedom and protection. They opened new schools and educational institutions in the suitable places as a results of the agreement. Missionary activities and schools run by Jesuit Missionaries in the Ottoman Empire considerably increased during the Sultan Abdulhamit II. Jesuit Missionaries, who took responsibility to protect the French people, continued their educational activities in Kayseri, one of the old and historic cities of Anatolia. They bought or rent lands and then erected buildings in Kayseri to continue their educational activities. They obtained permission and certificate from the goverment to legalize their presence. Then these constructions bought by the missionaries were turned into schools in oder to operate their activities in Kayseri. The purpose of this study is to uncover missionary activities which has long been the missing topic in the Ottoman studies. This paper mainly concerns reactions of Ottoman goverment towards Jesuit Missionaries, their activities and developments in the Kayseri by uncovering new and different archival and monographical sources. Öz XVI. yüzyıl sonlarında Osmanlı topraklarında faaliyet gösteren Katolik Cizvit Misyonerleri kapitülasyonların kendilerine tanıdığı “din ve inanç özgürlüğü” ifadesini tek taraflı olarak esnetmek suretiyle hızla okullaşmaya başlamışlar ve kendileri için uygun olan yerlerde merkezler oluşturmuşlardır. II. Abdülhamit döneminde misyonerlerin açtıkları okullarda gözle görülür bir artış olmuştur. Anadolu’nun en eski yerleşim yerlerinden olan Kayseri’de de Fransa’nın koruyuculuğunu üstlendiği Cizvit Misyonerlerinin eğitim faaliyetlerine hız verdikleri görülmektedir. Kayseri’de faaliyet gösteren Cizvit Misyonerleri eğitim alanındaki çalışmalarını, arsa ve arazi kiralamak ya da satın almak suretiyle elde edilen mekanlarda sürdürmekteydiler. Bu bağlamda mesken yapmak için izin ve ruhsat aldıkları ve daha sonra ise bu meskenleri birleştirme yoluna giderek okula dönüştürdükleri görülmektedir. Bu çalışmada Cizvit Misyoner okullarına karşı devletin aldığı tedbirler ve misyonerlerin çabaları arşiv ve monografik kaynakları ışığında irdelenmektedir.